Breastfeeding Self-Efficacy Related to Postpartum Depression Tendency - Anjani, Arum Yunia; Kostania, Gita; Toyibah, Afnani (Poltekkes Kemenkes Surakarta, 2025)
Background: Postpartum depression (PPD) is a psychological disorder that is related to insecure relationships, mother-child bonding disorders, and also has an impact on increasing the risk of maternal suicide. Breastfeeding self-efficacy (BSE) is related to physical and psychological adjustment in postpartum mothers and is one of the factors that can influence postpartum depression, plus breastfeeding is one of the main tasks of every postpartum mother. The purpose of this study was to analyze the relationship between breastfeeding self efficacy and tendency of postpartum depression at PMB S Blimbing District, Malang City, Indonesia. Methods: The study had used correlational analytic design with a cross sectional. The number of samples were 48 people, done by quota sampling technique. The tool of collecting data was questionnaire by Breastfeeding Self Efficacy Scale-Short Form (BSES-SF) and Edinburgh Postnatal Depression Scale (EPDS). Analysis data procedure was using spearman correlation test. Results: Data showed the age range of respondents were 20-35 years(83.3%); senior high school (50%); not working (75%); multipara (77.1%); high breastfeeding self efficacy (66.7%); not tendency of postpartum depression (81.2%); and respondent with high BSE who experienced not tendency of PPD (66.6%). The result showed there was a relationship between breastfeeding self efficacy and tendency of postpartum depression (p=0.000). Conclusion: Based on result of study, it is known that respondent who have high BSE came from respondents who not tendency of PPD. It means that BSE is one of the factors that can influence postpartum depression and it is impotant to scale up.